(untitled) (Malaysian Journal of Learning and Instruction, 2004)
The paper attempts to describe the relation of apposition in Malay. Whilst other relations such as coordination, modification and relative clauses have been widely discussed in the grammatical description of Malay, apposition has been largely left out. The isolation, as a guess, may be due to the fact that some appositional constructions may lie on boundary with other well-established relations, thus lessening the need for its explicit mention. We show in this paper the boundaries of apposition with these relations. Then, using data extracted from a 450,000 word corpus, we put forward the realizations of apposition in the Malay language from syntactic, semantic and pragmatic perspectives in order to close the structural gap currently existing in Malay grammatical relations. We end the paper by briefly mentioning some possible implications of this ’discovery’.